MicroRNA profiling provides insights into post-transcriptional regulation of gene expression in chickpea root apex under salinity and water deficiency - Hitaishi Khandal (Nature Portfolio, 2017)
Abstract Activity of root apical meristem (RAM) at the root apex is critical for stress-mediated modulation of root-architecture. Chickpea, like other legumes, possesses a basic open root meristem. Deep sequencing was used to perform microRNA expression profiling in root apex of chickpea (Cicer arietinum L.) in order to investigate post-transcriptional regulation of gene expression in this tissue in response to salinity and water deficit. Five small RNA libraries prepared from chickpea root apices at different stages of stress treatments were sequenced to obtain 284 unique miRNA sequences including 60 novel miRNAs belonging to total 255 families. Two hundred and fiftynine miRNAs were differentially expressed in stress. Six hundred and nine mRNA targets involved in diverse cellular processes were predicted for 244 miRNAs. Stress-responsive expression patterns of selected miRNAs, inverse expression patterns of their target genes and the target-cleavage sites were validated. Three candidate miRNA-target gene relationships were validated in transient expression system in chickpea. The miRNA expression profiling under salinity and water deficiency in a legume root apex and the reported function of their target genes suggested important roles of miRNA-mediated post-transcriptional regulation of gene expression involved in re-patterning of root hair cells, lateral root formation and high-affinity K+-uptake under these stresses.